PENERAPAN METODE TARTILA DALAM MENINGKATKAN KEMAMPUAN BACA TULIS AL-QUR'AN - Ach. Afifi; Moh. Ulum; M. Mahbubi (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to investigate the application of the Tartila method in enhancing the ability to read and write the Qur'an at MIN 1 Probolinggo using a qualitative approach. The Tartila method, which emphasizes gradual and structured learning, is designed to assist students in understanding and mastering the recitation of the Qur'an, while also facilitating their ability to write the Qur'anic verses accurately and properly. In this study, data were collected through in-depth interviews and direct observations involving the head of the madrasa, the head of the TPQ, and teachers who serve as Tartila instructors. The main focus of this study is to evaluate the impact of applying the Tartila method on students' Qur'anic reading and writing skills. The results of the study indicate that the implementation of the Tartila method has a significant influence in improving students' reading and writing abilities, as well as deepening their understanding and spiritual appreciation of the content and meaning of the verses they read and write. This method has proven effective in helping students memorize and write the Qur'an in an easier and more structured manner. Furthermore, the study also shows that learning using the Tartila method can enhance students' motivation and interest in Qur'anic studies. It is hoped that the findings will contribute significantly to the development of more innovative and effective Qur'anic teaching methods in the future